Pengembangan Ekonomi Desa melalui Kampung Garam (Studi Kasus Desa Bunder Kecamatan Pademawu Kabupaten Pamekasan Madura) - Wahyurini, Endang Tri; Hamidah, Emmy (Kadiri University, 2020)
The purpose of this research was to obtain an overview and analyze the patterns of economic development in the village of Bunder, Pademawu Pamekasan District. The research employed descriptive analytical-qualitative methods. The research illustrated that the village of Bunder was a village on the coast with considerable salt potential. The majority of the people earned their living as salt farmers. Based on the Pamekasan Regent program to facilitate the management and economic development in the village, a thematic village was formed, the formation of these thematic villages based on the local potential of the region. Therefore, the village of Bunder was designated as